2019
DOI: 10.1161/atvbaha.119.312399
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial Cell Atlas of wt (Wild Type) and ApoE (Apolipoprotein E)-Deficient Mice Defined by Single-Cell RNA Sequencing

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 74 publications
2
102
0
Order By: Relevance
“…Other studies have focused on the non-EC compartments in the atherosclerotic plaques. Working on the ApoE −/− atherosclerosis mouse model, Gu and co-workers found that non-immune cells also appear in a pro-inflammatory and stem-/progenitor-like state that is typified by the expression of stem cell antigen 1 (SCA1) in SMCs [52]. Moreover, isolated SCA1 + SMCs had high CCL2 expression in vitro, consistent with the pro-inflammatory signature.…”
Section: Atherosclerosismentioning
confidence: 90%
See 1 more Smart Citation
“…Other studies have focused on the non-EC compartments in the atherosclerotic plaques. Working on the ApoE −/− atherosclerosis mouse model, Gu and co-workers found that non-immune cells also appear in a pro-inflammatory and stem-/progenitor-like state that is typified by the expression of stem cell antigen 1 (SCA1) in SMCs [52]. Moreover, isolated SCA1 + SMCs had high CCL2 expression in vitro, consistent with the pro-inflammatory signature.…”
Section: Atherosclerosismentioning
confidence: 90%
“…Moreover, isolated SCA1 + SMCs had high CCL2 expression in vitro, consistent with the pro-inflammatory signature. Other cell types such as resident macrophages were also in an activated pro-inflammatory state [52]. While Western diet or ApoE knockout mouse models do not result in formation of progressive atherosclerotic lesions, these models nevertheless provide important insights into its early development and first-wave responses of ECs and SMCs to atherosclerosis development.…”
Section: Atherosclerosismentioning
confidence: 99%
“…They play a role in vasomotion, homeostasis and permeability of the vasculature [11]. The heterogeneity of perivascular cells has been unclear for many years, but recent single-cell RNA-sequencing data suggest that various, previously unknown, perivascular mesenchymal populations exist [28,29]. We have reported that Gli1 marks a specific perivascular cell type that drives cardiac fibrosis and vascular calcification [30,31].…”
Section: Cardiac Fibrosismentioning
confidence: 95%
“…In rodents model of arterial injury, perivascular administration of mesenchymal cells overexpressing VEGF around injured arteries increased adventitial blood vessels and macrophage recruitment [ 31 ]. In a model of atherosclerosis, single-cell RNA sequencing of aortic adventitia from wild type and ApoE (apolipoprotein E)-deficient mice identified a pro-inflammatory subset of adventitial fibroblasts expressing chemokines such as CCL2, essential for the recruitment of monocytes, further suggesting a causal role for adventitial fibroblasts in inflammation [ 32 ] ( Figure 1 b).…”
Section: Interaction With Immune Cells In the Perivascular Spacementioning
confidence: 99%